Mandibular molar uprighting using orthodontic miniscrew implants: a systematic review - Panagiota Magkavali-Trikka; Georgios Emmanouilidis; Moschos A. Papadopoulos (SpringerOpen, 2018)
Abstract The purpose of this systematic review was to identify studies and present the use of miniscrew implants (MIs) as an alternative treatment to mandibular molar uprighting. An electronic search and handsearching were conducted by two independent reviewers to identify relevant articles, published up to January 27, 2017. In order to methodologically assess the eligible studies, a pilot checklist consisting of 22 items was also implemented. After exclusion of all the irrelevant papers, only 17 studies were included, presenting 27 cases of mandibular molar uprighting in all planes using both direct and indirect force traction by MIs. Regarding the quality evaluation, the mean score of the included studies was 13.2, indicating a rather poor methodology implemented in the majority of the included cases. Due to many advantages, MIs provide a unique treatment alternative and constitute a reliable solution for treating tipped or impacted molars. Regarding the force application, a direct method is simpler, as it requires one MI and a single bracket or button, minimizing the patient's discomfort and also reducing chair time compared to more complex indirect anchorage. It also eliminates the possibility of unwanted movement of the anchorage unit, which can occur even with indirect anchorage as a result of technical errors. However, direct anchorage has limitations in cases of lingually tipped or rotated molars because a single force may be insufficient to upright the tooth.